2021
DOI: 10.1371/journal.pone.0246232
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and association mapping for iron toxicity tolerance in rice

Abstract: Iron (Fe) toxicity is a major abiotic stress which severely reduces rice yield in many countries of the world. Genetic variation for this stress tolerance exists in rice germplasms. Mapping of gene(s)/QTL controlling the stress tolerance and transfer of the traits into high yielding rice varieties are essential for improvement against the stress. A panel population of 119 genotypes from 352 germplasm lines was constituted for detecting the candidate gene(s)/QTL through association mapping. STRUCTURE, GenAlEx a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…From these and other studies it can be concluded that ample genetic variation for tolerance to Fe toxicity exists within theO. sativa gene pool (Matthus et al 2015;Pawar et al 2021), and that wild relatives may serve as sources of novel traits enhancing adaptation to Fe toxicity (Bierschenk et al 2020;Wairich et al, 2021).…”
Section: Siliconmentioning
confidence: 87%
See 3 more Smart Citations
“…From these and other studies it can be concluded that ample genetic variation for tolerance to Fe toxicity exists within theO. sativa gene pool (Matthus et al 2015;Pawar et al 2021), and that wild relatives may serve as sources of novel traits enhancing adaptation to Fe toxicity (Bierschenk et al 2020;Wairich et al, 2021).…”
Section: Siliconmentioning
confidence: 87%
“…6 implications for rice breeding 6 .1 Tolerance within the Oryza gene pool Numerous studies have screened sets of varieties or larger germplasm collections in attempts to identify donors for Fe toxicity, typically employing one of two main screening strategies. They may have been conducted in the field in Fe toxic hotspots, evaluating grain yield in addition to biomass and leaf symptoms (Melandri et al, 2021;Pawar et al 2021;Sikirou et al 2018), or they were designed as rapid screens in nutrient solution to which excess Fe had been added at high concentrations for short periods of time (Dufey et al 2015;Matthus et al 2015). From these and other studies it can be concluded that ample genetic variation for tolerance to Fe toxicity exists within theO.…”
Section: Siliconmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic diversity and structure of the population will be helpful for detecting marker-trait association which could be useful for trait enhancement in molecular breeding programs. In order to avoid spurious association of marker-phenotype in a population, population structure (Q) with relative kinship (K) analyses is essential to check the correctness of the panel population composition for linkage disequilibrium (LD) mapping analyses 50,51,52 . Thus, association estimate based on both the models of Generalized linear model (GLM) and Mixed linear model (MLM) is considered appropriate for mapping complex traits that have shown to perform better than other model analyses.…”
mentioning
confidence: 99%